2010
DOI: 10.1007/s00217-010-1222-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting direct and indirect methods for the estimation of the total carotenoid concentration in dried pastas

Abstract: The total carotenoid concentration (TCC) of several commercially available dried pastas prepared with or without eggs was assessed by means of the two wellestablished destructive approaches [spectrophotometry (SP) and high-performance liquid chromatography (HPLC)] and three non-destructive, direct (i.e., no sample preparation required) methods (resonance Raman spectroscopy, photoacoustic (PA) spectroscopy and colorimetry). The results obtained by the three direct methods correlate well with the TCC of investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Recently, Raman spectroscopy has been applied for quantitative analysis of sugars (Batsoulis et al, 2005;Wang, Mizaikoff, & Kranz, 2009) carotenoids (Bhosale et al, 2004;Dóka et al, 2010)and fatty acids (Afseth, Segtnan, Marquardt, & Wold, 2005)amongst others. However, quantitative analysis by absolute Raman intensity does not show good correlation because it is dependent on a number of factors such as experimental effects and laser power.…”
Section: Laser Power Dependency Of Raman Intensity and Band Ratiomentioning
confidence: 99%
“…Recently, Raman spectroscopy has been applied for quantitative analysis of sugars (Batsoulis et al, 2005;Wang, Mizaikoff, & Kranz, 2009) carotenoids (Bhosale et al, 2004;Dóka et al, 2010)and fatty acids (Afseth, Segtnan, Marquardt, & Wold, 2005)amongst others. However, quantitative analysis by absolute Raman intensity does not show good correlation because it is dependent on a number of factors such as experimental effects and laser power.…”
Section: Laser Power Dependency Of Raman Intensity and Band Ratiomentioning
confidence: 99%
“…There is much debate about the reliability of indirect measurement techniques, such as HPLC. For instance, when HPLC was compared with direct measurements of total carotenoid content in pastas using photo acoustic (PA) spectroscopy and colorimetry [16], HPLC was able to detect total carotenoid concentration in only six wheat samples among the 13 samples analysed, whereas PA spectroscopy and colorimetry showed measurable signals for all 13 samples. Indeed, the milling process, which is necessary for HPLC analysis, is known to affect wheat quality.…”
Section: Nutritional Analysesmentioning
confidence: 99%
“…This was demonstrated by various authors through the optical characterizing of food products, such as marine algae, coffee, milk, cheese, yogurt, tortillas, maize, ketchup, pastas, chocolates, vegetables, etc. (Rosencwaig and Hall, 1975;Reis et al, 1986;Martel et al, 1987: Bicanic et al, 2011Dóka et al, 2010;2013;Hernández-Aguilar et al, 2011 ;. Likewise, few researches of PAS applied to the study of bread products have been found.…”
Section: Introductionmentioning
confidence: 99%